COMPARISON OF MICROVASCULAR FREE TISSUE TRANSFER IN ADULT AND PEDIATRIC PATIENTS - Rashid, Haroon Ur; Rashid, Mamoon; Rehman, Ishtiaq Ur; Yousaf, Shumaila; Khan, Nasir; Akhtar, Aqsa; Eitezaz, Farhan Ahmad (Journal of Ayub Medical College Abbottabad, 2019)
Background: Free tissue transfer is a routine practice in adults with good success rates. Further advances in techniques and microsurgical skills have proved that free tissue transfer in paediatric population is feasible, reliable and safe. Methods: This study is conducted to compare anastomosis duration, total general anaesthesia duration, hospital stay and outcomes of flaps (survival, partial loss, complete loss, complications ) in paediatric group ( age <15 years ) and adult group ( 15 -70 years age). All patients with large soft tissue defects, congenital defects , traumatic defects and post tumor extirpation were included in this study from December 1st 2017 to May 30th2018. These patients underwent different microsurgical procedures, the reconstructive armamentarium included use of Latissimus dorsi flap, Anterolateral thigh flap, Fibula flap, Radial forearm flap, functioning Gracillis muscle, iliac crest flap, Deep inferior epigastric artery perforator flap and Rectus abdominis muscle flap. Post-traumatic defects were the commonest indication of free tissue transfer in Paediatric population while post tumor extirpation defects were commonest defects encountered in adult population. Results: On average the total anaesthesia duration is slightly shorter in paediatric group than in adult patients while anastomosis duration is slightly shorter in adults then in paediatric patients .The overall complication rate is comparable in both groups and all the flaps survived well. Conclusion: Microsurgical free tissue transfer can be confidently attempted in children and their results are comparable with those of adult group.